FIELD STUDIES IN ORTAKOLO - Musaeva, M K; Magomedova, P M (History, Archeology and Ethnography of the Caucasus, 2016)
The article is devoted to ethnographic description of the economic and residential complex of Ortakolo farm, which was located in the mountain-and- valley area, dictating its own characteristics due to the lack of arable land: the artificially created terraced gardening and small-sized residential complexes in inarable land. Much attention is paid to traditional customs, concepts and ritual practices of the local gardeners.
Keywords: mountain-and-valley gardening; terraces; economic complex; small-sized residential space; customs and rites of gardeners